PI1M Refresher Workshop - Universiti Malaysia Sarawak, Institute of Social Informatics and Technological Innovations (Universiti Malaysia Sarawak (UNIMAS), 2013)
A refresher workshop conducted for PI1M Managers and Asst. Managers.